Effects of Aggregate Gradation on the Physical Properties of Semiflexible Pavement - Nadiah Md. Husain; Mohamed Rehan Karim; Hilmi B. Mahmud; Suhana Koting (Advances in Materials Science and Engineering)
Semiflexible pavement (SFP), a composite pavement, is formed by filling into a very open porous asphalt skeleton a specifically designed water consistency fluid mortar with a very high early and 28-day strength. The amalgamation of both components will produce a SFP where it will replace the conventional wearing course. The main goal of this investigation is to study the effect of various aggregate gradations towards producing SFP. These include determining the optimum binder, volumetric properties, and durability and strength of each aggregate gradation. The final results were statistically analyzed and two factor variance analyses (ANOVA) were performed to check on the significance at certain confidence limits. The results confirmed that different aggregate gradations significantly affect the properties mentioned.